Analysis of the Development Needs of E-Book Story Media 'BUCETAR' (Picture Story Books) for Elementary School Students in Indonesian Schools Riyadh - Rohmah, Fita Nur; Istiq'faroh, Nurul; Subrata, Heru (Journal of Innovation and Research in Primary Education, 2025)
This study aims to analyze the initial needs in the development of e-book story media "BUCETAR" as a means of learning thematic literacy for elementary school students at Sekolah Indonesia Riyadh. The background of this research is based on the importance of contextual and interesting digital-based learning media innovations to improve students' literacy skills, especially in the context of Indonesian Overseas Schools (SILN). This study uses a descriptive qualitative approach with data collection techniques in the form of observation, semi-structured interviews, and the distribution of questionnaires to grade 4 students and teachers. The results of the observation show that the learning process is still conventional with the minimal use of digital media. Teachers are aware of the importance of developing story-based media that is in line with the theme of the curriculum and the student experience. The results of the questionnaire showed that the majority of students liked picture stories, were interested in using e-books, and liked adventure topics that were relevant to their lives. The results of interviews and observations reinforce the finding that the learning media used has not been able to foster students' active involvement in the literacy process. Based on this needs analysis, the development of the "BUCETAR" e-book story is directed at the integration of narrative text with interesting illustrations, thematic approaches according to the curriculum, and interactive designs that support active student participation. This study recommends the development of e-book media as an alternative to literacy learning that is adaptive to technological developments and student needs in the SILN environment. In addition, the results of this study are the basis for further development and evaluation of the effectiveness of the media after it is implemented.